Rancang Bangun Aplikasi Edugame Peta Buta untuk Anak-Anak Berbasis Android - Muhammad Rinaldo Fernandes; Iskhaq Fitriansyah; Rachmansyah Rachmansyah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2016)
Related with information and communication technology development nowadays causes habitual and activity changing happen in daily life of people. One of that technology is mobile information and communication technology (hand phone) with purpose to understand that information to be learned. The problem that happening nowadays is children’s desire to learn about the study especially social lesson that has relationship with Indonesian map because of many aspects of knowledge in Indonesia itself so that knowledge is often obeyed and did not known yet. According to that aspect nowadays game is popular serving objectively. Such as edugame which is the game that create as learning facility through the game. So that’s why we need learning application to children that can entertain and pleasure them with include the lesson to the game so it can increase and improve the knowledge that related to Indonesian geography characters, to develop this application uses prototyping method which is the part of product that express logical even physical external that is shown.